Circulating visfatin level is associated with hepatocellular carcinoma in chronic hepatitis B or C virus infection. (February 2017) - Tsai, I-Ting; Wang, Chao-Ping; Yu, Teng-Hung; Lu, Yung-Chuan; Lin, Chih-Wen; Lu, Li-Fen; Wu, Cheng-Ching; Chung, Fu-Mei; Lee, Yau-Jiunn; Hung, Wei-Chin; Hsu, Chia-Chang
Abstract: Adipocytokines play an important role in adipose tissue homeostasis, especially in obesity-associated disorders such as non-alcoholic fatty liver and their complications including hepatocellular carcinoma (HCC). Although visfatin is an adipocytokine highly expressed in visceral fat that has been demonstrated to play a critical role in the progression of human malignancies, little is known about the role of visfatin in HCC associated with chronic hepatitis C virus (HCV) and hepatitis B virus (HBV) infection. In this study, we investigated whether plasma visfatin levels were altered in patients with HCC and the association between plasma visfatin levels and pretreatment hematologic profiles. Plasma visfatin levels were measured by enzyme-linked immunosorbent assays in 193 patients with different stages of HBV or HCV infection, and 92 healthy control subjects. The patients with HCC and chronic HCV or HBV infection had higher levels of visfatin than patients with HBV, HCV, and cirrhosis. In multivariate logistic regression analysis, levels of alpha-fetoprotein (AFP) (OR: 1.13, p = 0.003), and plasma visfatin (OR: 1.17, p = 0.046) were independently associated with HCC. Multiple stepwise regression analysis showed that plasma visfatin level was positively associated with age, aspartate aminotransferase to platelet ratio index (APRI), and AFP. Trend analyses confirmed that plasma visfatin concentration was associated with AFP > 8 ng/mL, cirrhosis, HCC, tumor size > 5 cm, and Barcelona Clinic Liver Cancer-C stage. These results suggested that the plasma visfatin level is associated with the presence of HCC, and that a higher plasma visfatin level may be important in the pathogenesis of HCC. Visfatin may act as both a protective and pro-inflammatory factor. Plasma visfatin concentration may serve as an additional tool to identify patients with more advanced necroinflammation.